8/3 * 2 - 6/7 * 1/3
giúp mình với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =5/6(1/8+2/3)=5/6*19/24=95/144
b: =3/4(7/5-1/2)=27/40
c: =35/24*2/3=35/36
<=>\(\left|\dfrac{1}{2}-2x\right|=\dfrac{5}{3}< =>\left[{}\begin{matrix}\dfrac{1}{2}-2x=\dfrac{5}{3}\\\dfrac{1}{2}-2x=\dfrac{-5}{3}\end{matrix}\right.< =>\left[{}\begin{matrix}2x=\dfrac{-7}{6}\\2x=\dfrac{13}{6}\end{matrix}\right.< =>\left[{}\begin{matrix}x=\dfrac{-7}{12}\\x=\dfrac{13}{12}\end{matrix}\right.\)
\(\left|\dfrac{1}{2}+2x\right|+\dfrac{2}{3}=\dfrac{7}{3}\)
\(\left|\dfrac{1}{2}+2x\right|=\dfrac{7}{3}-\dfrac{2}{3}=\dfrac{5}{3}\)
⇔\(\left[{}\begin{matrix}\dfrac{1}{2}+2x=\dfrac{5}{3}\\\dfrac{1}{2}+2x=-\dfrac{5}{3}\end{matrix}\right.\)
⇔ \(\left[{}\begin{matrix}x=\dfrac{7}{12}\\x=-\dfrac{13}{12}\end{matrix}\right.\)
Vậy ...
b: \(=\dfrac{3a-9-2a-6-6}{\left(a+3\right)\left(a-3\right)}=\dfrac{a-15}{a^2-9}\)
\(=-7\cdot\left[16+\left(-36\right):\left(-9\right)\right]+125=-77\cdot20+125=-140+125=-15\)